OPTIMALISASI PENGELOLAAN ARSIP FISIK DAN DIGITAL DI SEKOLAH DALAM ERA TRANSFORMASI DIGITAL - Rahmawati, Ima; Lestari, Hana; Nuraida S, Siti (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2025)
The research method used is a qualitative approach with a case study at the school. Data was collected through in-depth interviews with the school principal, administrative staff, and teachers, as well as direct observation of the existing archive management processes. The findings show that although SMAN 1 Cibungbulang has started to implement a digital system for archive management, there are still significant challenges, such as the lack of technical skills among some staff members, as well as issues in integrating physical and digital archives. However, the study also identifies the potential for improving efficiency and accuracy in archive management through optimization via information technology-based training, the implementation of an integrated archive management system, and improvements in digital infrastructure. Based on these findings, it is recommended that the school enhance staff training, strengthen secure digital storage systems, and develop policies that support the transition to comprehensive digital archive management.